Kemerdekaan Berfikir dalam Hak Asasi Manusia dan Islam - Wijaya, Arif (Prodi Siyasah Jinayah (Hukum Tata Negara dan Hukum Pidana Islam) Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2013)
Abstract: In Islam, reason is put on the most honor place and make it as one of the valuable means to realize the exixtance of God. It is inevitable that some of the Islamic teachings are mobilizing sense, opening mind, and opening human reason, body and soul. Islam does not like the people who do not use their minds, the people whose minds are bound by beliefs and isms that are not based on a correct basis. The independence of thinking can reinforce and strengthen the faith, humility and awareness of the greatness of Allah. Independence of thinking is quite important. Because without it, there would be no innovation and creativity. After 68 years of Indonesianâs independence politically, independence of thinking is something that needs to be realized. Without freedom of thinking and social justice, the so called independence is just imaging. Independence of thinking is a golden bridge towards a common welfare. Independence of thinking and freedom of expression are the right of every citizen to express their thoughts orally and in a written form freely in accordance with the provisions of the legislation in force.Keywords: Freedom of thinking, politics, human rights, Islam